Bahasa Indonesia Optimasi Kualitas Lem kertas PG 6802 ALV Menggunakan Pendekatan Pengukuran pH, Density, Solid Content dan Viskositas : optimasi kualitas lem kertas - Risma Sari; Armin, Muhammad Ikhlas; Saputra, Muhammad Alif (Median : Jurnal Ilmu Ilmu Eksakta, 2024)
Polymers are essential components in various aspects of human life, particularly in the production of different types of materials and products. One of the primary applications of polymers is in the manufacturing of adhesives or glues used to bond various substrates. PG 6802 ALV adhesive, for example, is widely used in the ceramic box industry. This research was conducted to test the characteristics of PG 6802 ALV adhesive in several production batches at PT. XYZ, namely batches 0119LSA001, 0219LSA002, and 0219LSA004. One of the measured parameters was the viscosity of the adhesive using a Brookfield viscometer with a spindle 0.4 at a speed of 10 rpm. The measurement results Brookfield viscometer with a spindle 0.4 at a speed of 10 rpm. The measurement results showed that the viscosity of PG 6802 ALV adhesive ranged between 10500 cps, 10400 cps, and 11600 cps. Additionally, measurements of the adhesive's solid content were obtained in the range of 60.40% to 60.95%. The density of PG 6802 ALV adhesive ranged from 1.0528 to 1.0705 g/ml, while the pH was in the range of 5. In conclusion, this research provides an overview of the physical and chemical characteristics of PG 6802 ALV adhesive in several production batches. The measurement results of viscosity, solid content, density, and pH provide important information for a better understanding of the properties of this adhesive. This knowledge can be utilized for the development of improved products and the enhancement of the production process in the ceramic box industry and other adhesive applications.